Relationship between Sensory Alterations and Repetitive Behaviours in Children with Autism Spectrum Disorders: A Parents’ Questionnaire Based Study - Anna Fetta; Elisa Carati; Laura Moneti; Veronica Pignataro; Marida Angotti; Maria Chiara Bardasi; Duccio Maria Cordelli; Emilio Franzoni; Antonia Parmeggiani (Brain Sciences, 2021)
The relationship between sensory profile and repetitive behaviours in autism spectrum disorder (ASD) has long been known. However, there is no consensus on the type of relationship that exists between them. This monocentric retrospective–prospective observational study aimed (a) to detect a clinical correlation between the severity of repetitive behaviours and the alterations of sensory profile in a sample of 50 children diagnosed with ASD; (b) to evaluate how different patterns of stereotypies and sensory alterations correlate with each other and with the main clinical–instrumental variables in the same sample. We enrolled 29 children in the retrospective phase of the study and 21 in the prospective phase. The Repetitive Behaviour Scale-Revised (RBS-R) and the Short Sensory Profile (SSP) were administered to the caregivers, and clinical–instrumental data were collected. SSP and RBS-R total scores directly correlated with a high significance rate. Among the subscales, the strongest correlations involved “Visual/Auditory Sensitivity”, related to “Stereotyped Behaviour” and “Sameness Behaviour”. “Under-Responsive/Seeks Sensation” related to “Stereotyped Behaviour”. Sex and intellectual disability significantly influenced both the stereotypies and the sensory alterations of the examined population. In conclusion, this study provides new insights into the relationship between sensory alterations and repetitive behaviours in ASD children by using direct medical observation and parent observation.